TAKBIRAN MASYARAKAT DESA KEBUNDURIAN KABUPATEN KAMPAR PADA MALAM IDUL FITRI - Amanan Amanan (Ensiklopedia Social Review, 2019)
Many ways are done by humanity to manifest gratitude to Allah SWT with the coming of the holy month of Ramadan, as well as the compilation of the end of the holy month of Ramadan which is celebrated on the 1st day of the year. Riau Province as a center of Malay language and culture (UU. Hamidy, 1988: 51) has many traditions. In order to welcome the holy month of Ramadan and also end a very lucky month there. Ramadhan and Eid al-Fitr, for example in the Kampar Kanan area (Kuok, Tiro Air Tiris, Rumbio, Bangkinang, etc.) in welcoming the holy month of Ramadhan there are visitors to the bath "Balimau", and the compilation of the holy month has also ended there is also a community tradition now announce the Feast, the six-day circumcision fast, and so on. Kampar Kanan people in Kampar Regency hold fasting for one month and after Ramadan fasting they end their victory on the Shawwal every year. The second day on 2 Shawwal, the people in Kampar RIGHT were fasting for 6 days. On the 7th day (8th Eid) they celebrated with great fanfare. So on the 8th Eid day of Eid al-Fitr in this area it was very lively, it usually happens because they combine Eid al-Fitr with the sixth fasting day. In addition, people in Bengkalis Regency, Siak Regency, Meranti Islands Regency and Pekanbaru City also held various activities, one of which was a "lompu colok" competition. This "Batobo Gulai" cuisine welcomes and celebrates the holy month of Ramadan to Eid with various traditions. One of the traditions is takbir house-to-house in the evening of Eid.